2020
DOI: 10.1111/jace.16994
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoluminescence quantum yield of red‐emitting CdTe:Gd3+ QDs for WLEDs applications

Abstract: In order to improve the quantum yield of red‐emitting CdTe quantum dots (QDs), CdTe:Gd3+ QDs were synthesized by a facile one‐step aqueous method. The composition, morphology, and photoluminescence property of CdTe:Gd3+ QDs were characterized. The results show that the doping of Gd3+ not only leads to a red‐shift in the emission wavelength but also improves the photoluminescence quantum yield (PL QY) of CdTe QDs up to 85.74%. Doping of Gd element causes the Te dangling bond on the surface of CdTe QDs to be des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…At present, it has been reported that CdTe QDs are dispersed in organic or inorganic substrates, such as PVA, 13 NaCl, 14 CaCO 3 15 and BaSO 4, 16 to prepare high‐emitting solid quantum dot phosphors. The CdTe QDs‐based solid‐state composites can be used as converted phosphors for LED and indoor plant growth application 17,18 . In our previous work, we developed a simple precipitation method that allows us to obtain large‐scale NaNO 3 19 and CaCO 3 20 composite powders based on CdTe QDs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it has been reported that CdTe QDs are dispersed in organic or inorganic substrates, such as PVA, 13 NaCl, 14 CaCO 3 15 and BaSO 4, 16 to prepare high‐emitting solid quantum dot phosphors. The CdTe QDs‐based solid‐state composites can be used as converted phosphors for LED and indoor plant growth application 17,18 . In our previous work, we developed a simple precipitation method that allows us to obtain large‐scale NaNO 3 19 and CaCO 3 20 composite powders based on CdTe QDs.…”
Section: Introductionmentioning
confidence: 99%